The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations ON FRESH AIR Keep windows open as much as possible. Occasionally the noise and dust of traffic make this impossible during the middle of the day. Air that is kept moving is invigorating. [illustration] Use a vacuum cleaner. ON DUST Dust may carry germs; it irritates the throat and nose and may reach the lungs. Thus it may infect the body or make it more liable to infection. Search for hidden dust and dirt, and remove it; if you cannot prevent it from collecting, clean it out frequently. The electric vacuum cleaner provides the most hygienic way of getting rid of dust without causing some of it to get into the air. Some clubs and Women's Institutes own a vacuum cleaner which may be hired for a small payment; and sometimes it is possible to hire one from a shop. Find out what is possible in your own neighbourhood. ON CLEANSERS Soap and water are the best cleansers of the house. Sunlight and fresh air are the best cleansers of a stuffy room. Several special soaps to suit the different jobs to be done (such as flakes, powders, scouring powders, household and toilet soaps) are on sale. Polish keeps dust from accumulating in crevices and preserves the wood of floors and furniture. Dust and spilt liquids can be easily wiped from a polished surface. Varnished paintwork should also be polished. 4 177/5/8/2